Hydrolyzed Infant Formula and Early β-Cell Autoimmunity: A Randomized Clinical Trial - Knip, Mikael (JAMA, 2014)
IMPORTANCE: The disease process leading to clinical type 1 diabetes often starts during the first years of life. Early exposure to complex dietary proteins may increase the risk of β-cell autoimmunity in children at genetic risk for type 1 diabetes. Extensively hydrolyzed formulas do not contain intact proteins. OBJECTIVE: To test the hypothesis that weaning to an extensively hydrolyzed formula decreases the cumulative incidence of diabetes-associated autoantibodies in young children. DESIGN, SETTING, AND PARTICIPANTS: A double-blind randomized clinical trial of 2159 infants with HLA-conferred disease susceptibility and a first-degree relative with type 1 diabetes recruited from May 2002 to January 2007 in 78 study centers in 15 countries; 1078 were randomized to be weaned to the extensively hydrolyzed casein formula and 1081 were randomized to be weaned to a conventional cows’ milk–based formula. The participants were observed to April 16, 2013. INTERVENTIONS: The participants received either a casein hydrolysate or a conventional cows’ milk formula supplemented with 20% of the casein hydrolysate. MAIN OUTCOMES AND MEASURES: Primary outcome was positivity for at least 2 diabetes-associated autoantibodies out of 4 analyzed. Autoantibodies to insulin, glutamic acid decarboxylase, and the insulinoma-associated–2 (IA-2) molecule were analyzed using radiobinding assays and islet cell antibodies with immunofluorescence during a median observation period of 7.0 years (mean, 6.3 years). RESULTS: The absolute risk of positivity for 2 or more islet autoantibodies was 13.4% among those randomized to the casein hydrolysate formula (n = 139) vs 11.4% among those randomized to the conventional formula (n = 117). The unadjusted hazard ratio for positivity for 2 or more autoantibodies among those randomized to be weaned to the casein hydrolysate was 1.21 (95% CI, 0.94–1.54), compared with those randomized to the conventional formula, while the hazard ratio adjusted for HLA risk, duration of breastfeeding, vitamin D use, study formula duration and consumption, and region was 1.23 (95% CI, 0.96–1.58). There were no clinically significant differences in the rate of reported adverse events between the 2 groups. CONCLUSIONS AND RELEVANCE: Among infants at risk for type 1 diabetes, the use of a hydrolyzed formula, when compared with a conventional formula, did not reduce the incidence of diabetes-associated autoantibodies after 7 years. These findings do not support a benefit from hydrolyzed formula. TRIAL REGISTRATION: clinicaltrials.gov Identifier: NCT00179777